Exploration of porang plant population and productivity in different locations in the Buton island - Yuniati, Sri; Roeswitawati, Dyah; Husein, Syarif; Ikhwan, Ali; Chuzaimah, Chuzaimah; Diana, Susanti; Rosmawati, Henny; Sebayang, Nico Syahputra; Marlina, Neni; Melis, Juliano van (Environmental and Agriculture Management, 2024)
The productivity of porang plants in Buton Island is influenced by varying environmental conditions across different locations, leading to inconsistent yields. The objective of this study was to explore the population and productivity of porang plants in distinct environments on Buton Island. This study used field surveys and secondary data collection to assess plant density to evaluate growth conditions. The collected data were analyzed using simple statistics and displayed on a population map. The results showed that there were 17 porang cultivation locations spread across five sub-districts with a population of 35.000-60.000. The conclusion emphasizes the importance of site-specific agricultural strategies for optimizing porang productivity. This research impacts sustainable agricultural practices, particularly in regions with varying environmental condition